2017
DOI: 10.1186/s13104-017-3001-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antifungal activities and phytochemical profile of leaf extract from different extractants of Ricinus communis against selected pathogens

Abstract: Objectives: Ricinus communis leaves are used in herbal preparations for treating candidiasis, skin and wound infections in Ghana. This study aimed at comparing the phytochemical profile of aqueous, methanol, petroleum ether, ethyl acetate and ethanolic extracts of the leaves of Ricinus communis and determine the growth inhibitory activities, bactericidal, bacteriostatic and fungicidal effects of the respective extracts on Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonaie an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 12 publications
6
73
0
1
Order By: Relevance
“…In R. communis extract, the highest test concentration had remarkably greater growth inhibition than the lower concentrations (Table 2). Similar antibacterial activity of E. citriodora Ghaffar et al, 2015) and R. communis (Suurbaar et al, 2017) leaf extracts has been reported against both Gram negative and positive bacterial pathogens of humans such as Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Aspergillus niger and Rhizopus solani. Moreover, the two upper test concentrations (100 and 50 mg mL -1 ) of L. camara and J. schimperiana revealed significantly higher growth inhibition within a species than the remaining lower test concentrations (Table 2).…”
Section: Antibacterial Activity Assaysupporting
confidence: 73%
See 1 more Smart Citation
“…In R. communis extract, the highest test concentration had remarkably greater growth inhibition than the lower concentrations (Table 2). Similar antibacterial activity of E. citriodora Ghaffar et al, 2015) and R. communis (Suurbaar et al, 2017) leaf extracts has been reported against both Gram negative and positive bacterial pathogens of humans such as Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Aspergillus niger and Rhizopus solani. Moreover, the two upper test concentrations (100 and 50 mg mL -1 ) of L. camara and J. schimperiana revealed significantly higher growth inhibition within a species than the remaining lower test concentrations (Table 2).…”
Section: Antibacterial Activity Assaysupporting
confidence: 73%
“…Extracts of E. citriodora and R. communis found to have alkaloids, flavonoids, phenols, saponins, tannins and terpenoids (Table 1). Javed, Shoaib, Mohmood, Mushtaq, and Iftikhar (2012) and Suurbaar, Mosobil and Donkor (2017) have found out similar constituents of E. citriodora (except tannins) and R. communis leaf extracts, respectively. Unlike the present study, alkaloids, tannins and terpenoids are absent from the methanol leaf extract of E. citriodora (Pathmanathan, Uthayarasa, Jeyadevan, & Jeyaseelan, 2010).…”
Section: Extract Yieldmentioning
confidence: 90%
“…The method described by Suurbaar et al [19] was applied to explore the antifungal activity of aloin A. The fungal spores were washed from the surface of agar plates with sterile 0.85% saline containing 0.1% Tween 80 (v/v).…”
Section: Test For Antifungal Activitymentioning
confidence: 99%
“…Using the method described by Suurbaar et al [19], inoculum for the MIC and MBC test was prepared. At least three to five well isolated colonies of the same morphology from agar plate culture were taken.…”
Section: Inoculum Preparation For Minimum Inhibitory Concentration (Mmentioning
confidence: 99%
“…The anti-fungal property of a plant extract is determined by the presence of compounds such as phenols, tannins, flavonoids, terpenoids, and saponins, and the methanol extract of plants has been recorded to contain high amount of these compounds [101,102]. Chicory (Cichorium intybus) is a plant that originated from the Iranian region and has been reported to have anti-fungal property [103].…”
Section: Antimicrobial Activitymentioning
confidence: 99%